Babasaheb Ambedkar writings and speeches (Maharashtra: Education Department Government of Maharashtra, 1982)
Contents:V.2. Dr.babasaheb ambedkar writings and speeches (xviii, 803 p.)
library has Volume-2 only.
Includes index.
Keywords: Political and social views; Ambedkar, B. R; Politics and government; Dalits--Social conditions; Statesmen--India